2011
DOI: 10.1093/ndtplus/sfr020
|View full text |Cite
|
Sign up to set email alerts
|

Yellow jacket envenomation-related acute renal failure

Abstract: We report a 58-year-old man with multiple yellow jacket stings who developed urticaria, renal failure, quadriparesis, rhabdomyolysis in succession. Investigations revealed renal and hepatic dysfunction, proteinuria, demyelinating polyradiculoneuropathy, acute tubular necrosis and glomerulonephritis. He improved with methylprednisolone, antihypertensives and two sessions of haemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Causes of venom-induced acute kidney injury in Asia includes snakes, hymenoptera, spiders, jellyfish and scorpions [ 37 , 42 ]. About 100 odd cases of Hymenoptera sting-related renal failure have been reported [ 43 ]. These stings cause renal involvement by pigment nephropathy, interstitial nephritis, rhabdomyolysis or intravascular haemolysis, vasculitis or direct toxin effect, which is similarly seen in scorpion stings.…”
Section: Nephropathymentioning
confidence: 99%
See 1 more Smart Citation
“…Causes of venom-induced acute kidney injury in Asia includes snakes, hymenoptera, spiders, jellyfish and scorpions [ 37 , 42 ]. About 100 odd cases of Hymenoptera sting-related renal failure have been reported [ 43 ]. These stings cause renal involvement by pigment nephropathy, interstitial nephritis, rhabdomyolysis or intravascular haemolysis, vasculitis or direct toxin effect, which is similarly seen in scorpion stings.…”
Section: Nephropathymentioning
confidence: 99%
“…In vitro studies of scorpion venom on human RBCs have shown haemolysis. Possible immune glomerulonephritis had been hypothesized since venom peptides can rarely induce an antigenic response [ 43 ]. Cytokine release and activation of complement cascade activation are known with some scorpion venoms but glomerulopathy per se has not been described in the literature.…”
Section: Nephropathymentioning
confidence: 99%
“…Two species of Vespa genus have been reported in Iran and Vespa orientalis or Cow wasp its local name Zar or Gunj is highly widespread [15][16][17][18][19]. Although many insects cause problems for human through stinging, but animals that more likely sting include honey bee, ordinary paper-making hornet wasps, yellow jacket and fire ants [20][21][22][23]. Fire ants of Pachycondyla sennaarensis species (Hymenoptera: Formicidae) living in Gheshm Island in Iran's territorial waters in Persian Gulf are considered one of the stinging ants [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Some species of Vespa genus have been reported in Iran (15)(16)(17)(18)(19)(20)(21). Bees and wasps, including honeybees, paper wasps, hornet wasps, yellow wasps, and fire ants are the insects, which more probably sting (22)(23)(24)(25)(26). Copyright Fire ants, Pachycondyla sennarensis, are considered as one of the sting agents in Gheshm island of the Persian Gulf (27)(28)(29)(30)(31)(32)(33).…”
Section: Introductionmentioning
confidence: 99%